1994
DOI: 10.1136/oem.51.5.347
|View full text |Cite
|
Sign up to set email alerts
|

Liver function tests and urinary albumin in house painters with previous heavy exposure to organic solvents.

Abstract: The serum activities or concentrations of aspartate aminotransferase (ASAT), alanine aminotransferase (ALAT), alkaline phosphatase (ALP), albumin, y-glutamyl transpeptidase (GGT), bilirubin (BIL), cholic acid (CHOL), chenodeoxycholic acid (CHENO), and transferrin with isoelectric point 5-7, and the urinary excretion of albumin were determined among male current or former house painters (n = 135) and house carpenters (n = 71) who had worked in their trades for at least 10 years before 1970. Workers who showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
45
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 35 publications
(9 reference statements)
5
45
2
Order By: Relevance
“…Mikkelsen et al 1988), there were reports of cerebral atrophy based on imaging techniques. These findings were not substantiated in a similar study (Lundberg et al 1995), and a principal conclusion of Ridgway et al (2003) was that the imaging techniques that had been used in these early studies were insensitive and unreliable. 12 Other names include organo-psycho syndrome (OPS), painters' syndrome, and solvent dementia.…”
Section: Persistent Cns Effectscontrasting
confidence: 37%
See 4 more Smart Citations
“…Mikkelsen et al 1988), there were reports of cerebral atrophy based on imaging techniques. These findings were not substantiated in a similar study (Lundberg et al 1995), and a principal conclusion of Ridgway et al (2003) was that the imaging techniques that had been used in these early studies were insensitive and unreliable. 12 Other names include organo-psycho syndrome (OPS), painters' syndrome, and solvent dementia.…”
Section: Persistent Cns Effectscontrasting
confidence: 37%
“…The principal concern for these solvents relates to the potential for some of the Category 3 solvents, in particular those with primarily C9-C11 aliphatic constituents, to cause chronic neurological effects in humans. As discussed in more detail in Section Persistent central nervous system effects, exposure to white spirit may have contributed to the neurobehavioral changes observed in house painters (Arlien-Soborg et al 1979, Hane et al 1977, Lindstrom and Wickstrom 1983, Lundberg et al 1995, Mikkelsen et al 1988, Seppalainen and Lindstrom 1982, but it seems more plausible that these changes were associated with periods of overexposure related to the use of aromatic-based solvent systems (Riala et al 1984) or periods of higher intensity exposure to other types of solvents during industrial spray painting (Elofsson et al 1980). Notably, repeated exposure studies in animals have not revealed any persistent functional changes or pathological findings (Kulig 1990, Nielsen et al 2006.…”
mentioning
confidence: 99%
See 3 more Smart Citations